Assessing the Use of Crushed Rock Aggregate and Carbon Black for Laterite Soil Stabilization in Road Construction. - Turyamureeba, Emmanuel (Kabale University, 2024)
The increased crushed rock aggregate consumption resulting from road construction has greatly contributed to the depletion of rocks in Uganda. The purpose of this research and design project was therefore to investigate the use of carbon black in the reduction of the amount of crushed rock aggregates used in the mechanical stabilization of suitable lateritic soils for road base construction. The lateritic soils were sampled from a borrow pit around Nyakambu 1 km from Kekubo town along Kekubo-Kikungiri Road. The crushed rock aggregates of size ranging from 0.075mm-10mm were obtained from the hipped quarry at the faculty of engineering which is about 2km from Kabale town off Kabale-Kisoro Road. Carbon black was sourced from GM Tire Recycling Plant, Njeru Eastern Uganda (00 22’42.9” N 330 08’10.4” E). Preliminary tests on the lateritic soil were carried out to determine if the soil required stabilization. The tests included Particle Size Distribution, Atterberg Limits, Maximum Dry Density, and California Bearing Ratio. The test results classified the soil as Clayey Gravel with Sand of high plasticity based on the Unified Soil Classification System (USCS) and it required stabilization for use on a road base. The combined effect of carbon black and crushed rock aggregates was investigated based on the compaction characteristics, Atterberg Limits, Particle size distribution, and California Bearing Ratio tests. Results obtained were analyzed graphically and a blend of 50% lateritic soil, 40% aggregates, and 10% carbon black was found to be the most effective in producing base material since it gave a CBR of 63.0 at 98% relative compaction and a PI of 6.5 which meet the requirements of CBR above 60 % as per the General Specifications for Road and Bridges of the Ministry of Works, Housing and Communication in Uganda. This research concluded that 50% lateritic soil, 40% crushed rock aggregates and 10% carbon black can be used for road base construction instead of 50% aggregates and 50% lateritic soil as per the research carried out by Jjuuko et al (2014). This therefore meant that there was a 10% reduction in crushed rock aggregate consumption. The research is considered a success because it met all the set objectives.